THE IMPACT OF WORK FAMILY CONFLICT AND JOB INSECURITY ON ORGANIZATION'S COMMITMENT WITH ROLE STRESS AS INTERVENING VARIABLE - Titik Inayati; Dina Apriliya (Manajemen dan Bisnis, 2017)
The purpose of this research is to know the impact of work family conflict and job insecurity towards organizational commitment with role stress as intervening variable (study at PT Mitra Kabel Indonesia in Surabaya). The Population in this study were 120 people. Data collected by giving of questionnaires to 56 people are married or have been married with the method of purposive sampling using likert scale 5 point for 19 statement items. Data analysis techniques with evaluation of measurement model, and AVE test. The results show that work family conflict has a positive and significant impact on the role of stress, Job insecurity has a positive and significant impact on the role of stress, role stress has positive and significant impact on organizational commitment, work family conflict has positive and insignificant impact on organizational commitment, job insecurity have a positive and insignificant impact on organizational commitment. Also, work family conflict and job insecurity have a positive and significant impact on organizational commitment with role stress as intervening variable.